On the centre of the cyclotomic Hecke algebras of $G(m,1,2)$ - McGerty, K (2010)
We compute the centre of the cyclotomic Hecke algebra attached to $G(m,1,2)$ and show that if $q ≠ 1$ it is equal to the image of the centre of the affine Hecke algebra $\Ha$. We also briefly discuss what is known about the relation between the centre of an arbitrary cyclotomic Hecke algebra and the centre of the affine Hecke algebra of type $A$.